2021
DOI: 10.1038/s41598-021-99773-0
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of Bursera morelensis and Lippia graveolens for the development of a new biopesticides in postharvest control

Abstract: Fruit and vegetable crops that are not consumed immediately, unlike other agricultural products, require economic and time investments until they reach the final consumers. Synthetic agrochemicals are used to maintain and prolong the storage life of crops and avoid losses caused by phytopathogenic microorganisms. However, the excessive use of synthetic agrochemicals creates health problems and contributes to environmental pollution. To avoid these problems, less toxic and environment-friendly alternatives are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 35 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…The essential oils (EOs) of the plants B. morelensis (voucher IZTA 42123) and L. grave-olens (voucher MCM8) were obtained by the hydrodistillation method. Subsequently, the essential oils were analyzed by gas chromatography/mass spectrometry (GC/MS) [ 15 ]. Of the essential oil components, five pure compounds present in one or both essential oils were selected.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The essential oils (EOs) of the plants B. morelensis (voucher IZTA 42123) and L. grave-olens (voucher MCM8) were obtained by the hydrodistillation method. Subsequently, the essential oils were analyzed by gas chromatography/mass spectrometry (GC/MS) [ 15 ]. Of the essential oil components, five pure compounds present in one or both essential oils were selected.…”
Section: Methodsmentioning
confidence: 99%
“…These strains were selected because they belong to the genus Fusarium , which has a tremendous economic impact on agriculture and produces many plant diseases [ 1 ]. Additionally, in the previous study of our research group, it was observed that they rapidly developed symptoms on a plant model and were highly sensitive to essential oils, which made them suitable test microorganisms for the study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations